Analisis Sistem Pendukung Keputusan dalam Penentuan Prioritas Pasien Hemodialisa Menggunakan Metode SAW - Novan Wijaya; Molavi Arman; Meiriyama (BETRIK, 2026)
Hemodialysis services for patients with chronic kidney disease require appropriate decision-making, especially in determining patient priorities when healthcare resources are limited. Subjective decision-making may lead to inaccuracies and potential inequality in healthcare services. Therefore, an information technology–based approach is needed to support a more objective and structured decision-making process. This study aims to implement the Simple Additive Weighting (SAW) method in a Decision Support System to determine the priority of hemodialysis patients. The study used sample data from five patients with five evaluation criteria, namely patient age, blood pressure, creatinine level, duration of kidney failure, and frequency of hemodialysis treatment. The analysis process includes the construction of a decision matrix, normalization of criteria values based on benefit and cost attributes, and calculation of preference values using weighted criteria. The results show that the SAW method can generate a clear priority ranking of patients. Based on the calculation results, patient A3 obtained the highest preference value of 0.92, followed by patient A1 with 0.88 and patient A5 with 0.87, indicating a higher urgency for receiving hemodialysis services. The implementation of this approach contributes to the development of health information technology, particularly in supporting more objective and transparent decision-making in hemodialysis patient management.